The International Sexual Health And REproductive Health during COVID-19 (I-SHARE) Study: A Multicountry Analysis of Adults from 30 Countries Prior to and During the Initial Coronavirus Disease 2019 Wave. (7th February 2022) - Toller Erausquin, Jennifer; Tan, Rayner K J; Uhlich, Maximiliane; Francis, Joel M; Kumar, Navin; Campbell, Linda; Zhang, Wei Hong; Hlatshwako, Takhona G; Kosana, Priya; Shah, Sonam; Brenner, Erica M; Remmerie, Lore; et al.
Abstract: Background: There is limited evidence to date about changes to sexual and reproductive health (SRH) during the initial wave of coronavirus disease 2019 (COVID-19). To address this gap, our team organized a multicountry, cross-sectional online survey as part of a global consortium. Methods: Consortium research teams conducted online surveys in 30 countries. Sampling methods included convenience, online panels, and population-representative. Primary outcomes included sexual behaviors, partner violence, and SRH service use, and we compared 3 months prior to and during policy measures to mitigate COVID-19. We conducted meta-analyses for primary outcomes and graded the certainty of the evidence. Results: Among 4546 respondents with casual partners, condom use stayed the same for 3374 (74.4%), and 640 (14.1%) reported a decline. Fewer respondents reported physical or sexual partner violence during COVID-19 measures (1063 of 15 144, 7.0%) compared to before COVID-19 measures (1469 of 15 887, 9.3%). COVID-19 measures impeded access to condoms (933 of 10 790, 8.7%), contraceptives (610 of 8175, 7.5%), and human immunodeficiency virus/sexually transmitted infection (HIV/STI) testing (750 of 1965, 30.7%). Pooled estimates from meta-analysis indicate that during COVID-19 measures, 32.3% (95% confidence interval [CI], 23.9%–42.1%) of people needing HIV/STI testing had hindered access, 4.4% (95% CI, 3.4%–5.4%) experienced partner violence, and 5.8% (95% CI, 5.4%–8.2%) decreased casual partner condom use (moderate certainty of evidence for each outcome). Meta-analysis findings were robust in sensitivity analyses that examined country income level, sample size, and sampling strategy. Conclusions: Open science methods are feasible to organize research studies as part of emergency responses. The initial COVID-19 wave impacted SRH behaviors and access to services across diverse global settings. Abstract : The I-SHARE-1 study in 30 countries assessed sexual and reproductive health outcomes among adults. During COVID-19 measures, 32.3% of people needing HIV/STI testing had hindered access, 4.4% experienced partner violence, and 5.8% decreased casual partner condom use.